2022
DOI: 10.1097/md.0000000000029722
|View full text |Cite
|
Sign up to set email alerts
|

White coat hypertension is another clinical characteristic of patients with inflammatory bowel disease: A cross-sectional study

Abstract: In this cross-sectional study, our aim was to analyze association of ambulatory blood pressure monitoring (ABPM) values with pulse wave velocity (PWV) in inflammatory bowel disease (IBD) patients as well as the prevalence and characteristics of white coat hypertension (WCH) in this group of patients with chronic inflammation and high prevalence of anxiety. We enrolled 120 consecutive IBD patients (77 Crohn´s disease; 43 ulcerative colitis) who were not treated with antihypertensive drugs without cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…A study on 120 patients with inflammatory bowel disease (IBD) by Premužić et al found that a significantly higher proportion of IBD patients with white coat hypertension had PWV values above the 8 m/s cutoff when compared to true normotensive IBD patients (84.8 vs 30.6, p < 0.001). Furthermore, IBD patients with white coat hypertension had significantly higher values of central SBP and central puls pressure when compared to true normotensive IBD patients, while having similar (nonsignificantly different) age, gender distribution, smoking status, duration of IBD, biochemical data, proportion of patients receiving biological or immunosuppressive treatment (11). Research by Stolarz et al compared PWV in a random sample of participants with either normotension, masked hypertension or white coat hypertension and found significantly higher values of PWV in patients with white coat hypertension when compared to those with true normotension (9.39+/-1.23 m/s vs 8.56+/-1.45 m/s; p < 0.05).…”
Section: Resultsmentioning
confidence: 90%
“…A study on 120 patients with inflammatory bowel disease (IBD) by Premužić et al found that a significantly higher proportion of IBD patients with white coat hypertension had PWV values above the 8 m/s cutoff when compared to true normotensive IBD patients (84.8 vs 30.6, p < 0.001). Furthermore, IBD patients with white coat hypertension had significantly higher values of central SBP and central puls pressure when compared to true normotensive IBD patients, while having similar (nonsignificantly different) age, gender distribution, smoking status, duration of IBD, biochemical data, proportion of patients receiving biological or immunosuppressive treatment (11). Research by Stolarz et al compared PWV in a random sample of participants with either normotension, masked hypertension or white coat hypertension and found significantly higher values of PWV in patients with white coat hypertension when compared to those with true normotension (9.39+/-1.23 m/s vs 8.56+/-1.45 m/s; p < 0.05).…”
Section: Resultsmentioning
confidence: 90%